2018
DOI: 10.1155/2018/4518541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Panton-Valentine Leukocidin Gene among Community AcquiredStaphylococcus aureus: A Real-Time PCR Study

Abstract: Panton-Valentine leukocidin (luk-pv) is a cytotoxin that causes leukocyte destruction and tissue necrosis. The aim of this study was to determine the prevalence of the pv1, mecA, and nuc genes in Staphylococcus aureus isolates obtained from anterior nares and superficial infection sites of skin in a slum population of West Bengal, India. Expression level of pv1 gene was also analysed. Twenty-two S. aureus strains were isolated, and phenotype and genotype specific examinations for S. aureus isolates were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…International Journal of General Medicine 2020:13 1350 performed. 20 Table 2 illustrates the base pair sequences of both primers.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…International Journal of General Medicine 2020:13 1350 performed. 20 Table 2 illustrates the base pair sequences of both primers.…”
Section: Dovepressmentioning
confidence: 99%
“…DNA samples to be run in PCR were diluted to10 ng/µL. 20 Multiplex conventional PCR was used for detection of mecA and PVL for all isolated S. aureus strains (24) by using the same primer as in Table 1, but with different PCR conditions, programmed in the protocol by Bhatta et al (2016) and illustrated in Table 3.…”
Section: Polymerase Chain Reaction (Real-time Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is significant variation in prevalence of PVL among S. aureus and methicillin-resistant S. aureus (MRSA) infections worldwide. Globally, prevalence of PVL toxin has been reported to increase across different countries such as Japan, USA, China, Germany, Egypt, Nigeria, and Kenya ranging from 12 to 90% [ 11 – 13 ]. Various studies have reported PVL prevalence with France at 5%, Bangladesh at 14.3%, Saudi Arabia at 8.1%, UK at 8.1%, Gambia at 72.9%, Nigeria at 10.7%, and Ghana at 75% [ 1 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…16s rRNA was used as the internal control (housekeeping gene). Primers for virulence genes were designed and synthesized (Sangon Biotech, Shanghai Co., Ltd.) according to previous reports ( Table 1; Ster et al, 2005;Karmakar et al, 2018). Real-time PCR was performed using the above prepared DNA intercalating fluorescent agent SYBR green for product detection.…”
Section: Regulation Of Virulence Genes Of S Aureus By Lab Strainsmentioning
confidence: 99%